Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fchem.2022.857348
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Investigation of the Reliability of the Frozen Nuclei Approximation for Short-Pulse Excitation: The Example of HCCI+

Abstract: In this work we quantitatively study the reliability of the frozen nuclei approximation for ultrafast dynamics. Specifically we study laser excitation of HCCI+ from its ground state to the first electronically excited state. The population of the first excited state is obtained by both the frozen nuclei approximation and by multidimensional nuclear dynamics. Detailed comparison of the results by the two methods are performed to provide quantitative criteria for the reliability of the frozen nuclei approximatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…[37,74] On the other hand, Jia et al have discussed the importance of the nuclear dynamics during laser-induced charge migration in HCCI + . [75][76][77] It has been shown that the overlap of the vibrational wave packets associated with the different electronic states during the nuclear dynamics leads electronic decoherence and recoherence. [75,76] Thus, ignoring the role of nuclear motion for charge migration occurring on 60 fs is not a good approximation.…”
Section: Discussionmentioning
confidence: 99%
“…[37,74] On the other hand, Jia et al have discussed the importance of the nuclear dynamics during laser-induced charge migration in HCCI + . [75][76][77] It has been shown that the overlap of the vibrational wave packets associated with the different electronic states during the nuclear dynamics leads electronic decoherence and recoherence. [75,76] Thus, ignoring the role of nuclear motion for charge migration occurring on 60 fs is not a good approximation.…”
Section: Discussionmentioning
confidence: 99%
“…The superposition between the X and A states of HCCI cation has been studied previously using high harmonic spectroscopy and advanced modeling. ( Kraus et al, 2015 ; Ding et al, 2017 ; Jenkins et al, 2018 ; Jia et al, 2019a ; Jia et al, 2019b ; Jia and Yang, 2022 ). However, due to the limited probing range of HHS, the wave packet motion beyond the first three femtoseconds has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Recent theoretical investigations suggested the coherence will rapidly dephase after 5 fs and even rephase at a later time. ( Jia et al, 2019a ; Jia et al, 2019b ; Jia and Yang, 2022 ). Therefore, a new probing method with attosecond time resolution and a long probing range is needed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations